PENGARUH MEKANISME CORPORATE GOVERNANCE TERHADAP KUALITAS LABA PADA PERUSAHAAN MANUFAKTUR - Azhari, Nurul; Asyik, Nur Fadjrih (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to test the influence of audit committee, institutional ownership, managerial ownership, and independent commissioner to the profit quality on the manufacturing companies in 2009-2013 periods.The samples are manufacturing companies which are listed in Indonesia Stock Exchange. The data is the secondary data which is in the form of audited financial statement in 2009-2013 periods and 21 companies have been selected as samples by using purposive sampling method. The independent variables in this research are audit committee, the institutional ownership, managerial ownership, and independent commissioner whereas the dependent variable is the profit quality. The data analysis has been done by using multiple linear regressions.The result of the research shows that audit committee, the institutional ownership, managerial ownership, and independent commissioner which have been included in the model are suitable to be used as the explanatory variable of profit quality. Partially, the managerial ownership has negative and significant to the profit quality which is measured by using discretionary accruals which means that when the managerial ownership is getting high, the discretionary accruals is getting low therefore it generates better profit quality and vice versa. Meanwhile, the audit committee, institutional ownership, and independent commissioner variables do not have any significant influence to the profit quality.Keywords: Audit Committee, Institutional Ownership, Managerial Ownership, Independent Commisioner, Profit Quality.